MiRNA 126 as a New Predictor Biomarker in Venous Thromboembolism of Persistent Residual Vein Obstruction: A Review of the Literature Plus a Pilot Study - Rossetti, Pietro; Goldoni, Matteo; Pengo, Vittorio; Vescovini, Rosanna; Mozzoni, Paola; Tassoni, Maria Ilaria; Lombardi, Maria; Rubino, Pasquale; Bernuzzi, Gino; Verzicco, Ignazio; Manotti, Cesare; Quintavalla, Roberto (Seminars in Thrombosis and Hemostasis, 2021)
Venous thromboembolism (VTE) is the third most common cardiovascular disease. Interleukins (ILs) and micro-ribonucleic acids (miRNAs) have been proposed as molecules able to modulate endothelial inflammation and platelet hyperactivity. At present, no early biomarkers are available to predict the outcome of VTE. We investigated in a pilot study a selected number of miRNAs and ILs as prognostic VTE biomarkers and reviewed literature in this setting. Twenty-three patients (aged 18–65) with a new diagnosis of non-oncological VTE and free from chronic inflammatory diseases were enrolled. Twenty-three age- and sex-matched healthy blood donors were evaluated as control subjects. Serum miRNAs (MiRNA 126, 155, 17.92, 195), inflammatory cytokines (IL-6, tumor necrosis factor-α, IL-8), and lymphocyte subsets were evaluated in patients at enrolment (T0) and in controls. In VTE patients, clinical and instrumental follow-up were performed assessing residual vein obstruction, miRNA and ILs evaluation at 3 months' follow-up (T1). At T0, IL-8, activated T lymphocytes, Treg lymphocytes, and monocytes were higher in patients compared with healthy controls, as were miRNA 126 levels. Moreover, miRNA 126 and IL-6 were significantly increased at T0 compared with T1 evaluation in VTE patients. Higher levels of MiR126 at T0 correlated with a significant overall thrombotic residual at follow-up. In recent years an increasing number of studies (case–control studies, in vivo studies in animal models, in vitro studies) have suggested the potential role of miRNAs in modulating the cellular and biohumoral responses involved in VTE. In the frame of epidemiological evidence, this pilot study with a novel observational approach supports the notion that miRNA can be diagnostic biomarkers of VTE and first identifies miRNA 126 as a predictor of outcome, being associated with poor early recanalization.
Keywords: micro-RNA; immunothrombosis; deep vein thromboembolism; residual vein obstruction; prognostic biomarker